PENGARUH ORGANIZATIONAL CAPITAL DAN TRANSFER PRICING AGGRESSIVENESS TERHADAP TAX AVOIDANCE - Fahri, Muhammad; Fahria, Rahmasari (Faculty of Economics and Business University of Mataram, 2023)
This study was conducted with the aim of obtaining empirical evidence regarding the factors that influence tax avoidance. The independent variables used in this study are organizational capital and transfer pricing aggressiveness. This study also uses control variables, namely leverage and profitability. This research is a type of quantitative research that uses secondary data in the form of annual reports and audited company financial reports. The objects selected in this study are manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2021 period. By using purposive sampling technique in determining the number of samples, 79 manufacturing sector companies were selected with a total of 237 research data. Multiple linear regression test technique was used in this study to test the effect of organizational capital and transfer pricing aggressiveness on tax avoidance. Hypothesis testing uses the help of Microsoft Excel and STATA MP version 17 applications. Based on the results of the data analysis that has been presented, this study provides the results that organizational capital and transfer pricing aggressiveness have no effect on tax avoidance.